Parent–Toddler Behavior and Language Differ When Reading Electronic and Print Picture Books - Strouse, Gabrielle A.; Ganea, Patricia A. (Frontiers in Psychology, 2017)
Little is known about the language and behaviours that typically occur when adults read electronic books with infants and toddlers, and which are supportive of learning. In this study, we report differences in parent and child behaviour and language when reading print versus electronic versions of the same books, and investigate links between behaviour and vocabulary learning. Parents of 102 toddlers aged 17 to 26 months were randomly assigned to read two commercially available electronic books or two print format books with identical content with their toddler. After reading, children were asked to identify an animal labeled in one of the books in both two-dimensional (pictures) and three-dimensional (replica objects) formats. Toddlers who were read the electronic books paid more attention, made themselves more available for reading, displayed more positive affect, participated in more page turns, and produced more content-related comments during reading than those who were read the print versions of the books. Toddlers also correctly identified a novel animal labelled in the book more often when they had read the electronic than the traditional print book. Availability for reading and attention to the book acted as mediators in predicting children’s animal choice at test, suggesting that electronic books supported children’s learning by way of increasing their engagement and attention. In contrast to prior studies conducted with older children, there was no difference between conditions in behavioural or off-topic talk for either parents or children. More research is needed to determine the potential hazards and benefits of new media formats for very young children.